Estetika Table Manner dalam Pendidikan Vokasi Pariwisata: Pendekatan Experiential Roleplay - Enny Karmin; Cipto Budi Handoyo (Journal of Tourism and Economic, 2025)
Table manner education is a fundamental component of tourism and hospitality education, particularly in shaping students’ interpersonal skills, professionalism, and competitiveness in the global hospitality industry. Since its establishment, Sekolah Tinggi Pariwisata AMPTA Yogyakarta has integrated an experiential learning approach through roleplay (Experiential Roleplay Approach) as part of its formal curriculum for hospitality students in the third semester. Furthermore, prior to formal academic enrollment, students are introduced to formal dining etiquette through industry exposure programs conducted at starred hotels. Although these practices have been consistently implemented, comprehensive academic research analysing the effectiveness of experiential roleplay in enhancing student engagement, conceptual understanding, and soft skills remains limited. This study aims to evaluate the effectiveness of the experiential roleplay approach within the context of vocational tourism education. The research employed a qualitative approach using a case study design, involving students from the Hospitality Study Program at AMPTA Yogyakarta. Data were collected through participatory observations of formal dining practice simulations, semi-structured interviews with students and instructors, and visual documentation. Thematic analysis was applied to identify patterns of engagement, concept retention, and professional attitude development. The findings reveal that the experiential roleplay approach significantly improves student learning engagement, accelerates the understanding of formal dining etiquette, and strengthens students' interpersonal skills. This study recommends reinforcing experiential learning methods within vocational education curricula to produce graduates who are adaptive, communicative, and competitive in the global workforce.